Atraumatic Occult Odontoid Fracture in Patients with Osteoporosis-Associated Thoracic Kyphotic Deformity: Report of a Case and Review of the Literature. (26th August 2015) - Mori, Kanji; Nishizawa, Kazuya; Nakamura, Akira; Imai, Shinji
Abstract : Anderson type II odontoid fractures are reported to be the most common injury of the odontoid process in patients over the age of 65. However, atraumatic occult Anderson type III odontoid fractures have been rarely described and remain a diagnostic challenge. In the present report, we illustrate a 78-year-old female with osteoporosis-associated marked thoracic kyphotic deformity who developed atraumatic Anderson type III occult odontoid fracture and raise awareness of this condition. Anteroposterior and lateral standard radiographs of cervical spine failed to disclose odontoid fracture. Magnetic resonance imaging demonstrated intensity changes of the axis. Subsequent computed tomography clearly demonstrated Anderson type III odontoid fracture. Conservative treatment achieved complete bone union without neurological deteriorations. At 3-year follow-up, the patient was doing well without neurological and radiological deteriorations. Even if the patients have no traumatic event, we have to keep odontoid fractures in our mind as one of the differential diagnoses when we encounter elderly patients with neck pain, especially in patients with osteoporosis-associated marked thoracic kyphotic deformity.